The effectiveness of treatment based on acceptance and commitment on rumination in women with a history of marital infidelity - Aghili, Seyed Mojtaba; Shakoori, Fatemeh; Asghari, Arezoo (Psychology of Woman Journal, 2022)
Marital infidelity is one of the most destructive problems in a relationship and one of the issues that usually leads to divorce. This study aimed to determine the effectiveness of acceptance and commitment therapy on rumination in women with a history of marital infidelity. The research method was quasi-experimental with a pre-test-post-test design with a control group. The research's statistical population comprised all women who experienced infidelity in the city of Bojnord who went to the counseling center in 2021 to receive counseling services. Among these, 40 people were selected by available sampling and randomly assigned to two groups experimental (20 people) and control (20 people). The research tool was Nolen and Hoeksma's (1989) rumination questionnaire. The research data were analyzed by multivariate analysis of covariance using spss-24 software. The findings showed a significant difference between the experimental and control groups in terms of rumination. In other words, treatment based on acceptance and commitment significantly reduced the rumination of women with a history of marital infidelity (p